The impact of internet communities through the electronic word of mouth - Samanta, Irene; Papageorgiou, Konstantinos (Archives of Business Research, 2020)
In this new technological era there have been new innovative methods which made their appearance and enabled marketers to have a more direct and intimate contact with customers using techniques beyond personal selling, advertising and sales promotion. This study has tried to explain the behaviour of internet community members in a variety of aspects imprinting behavioural levels on buying behaviour, socialization and trust mentality.